THE EFFECT OF FINANCIAL PERFORMANCE ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE: STUDY OF INDONESIA’S MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Wibowo, Panglima Zufar; Priyastiwi, Priyastiwi; Sutriyono, Agus Eko; Wardani, Sri (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
This research relied on an abundant phenomenon of the CSR disclosure on companies’ annual reports in the manufacturing sector since the CSR concept was more on the business organization agenda due to its ability to increase the competitiveness of a firm, especially in the manufacturing sector as one of the major sectors which dominate the business environment in Indonesia. This research aimed to examine the effect of financial performance on corporate social responsibility disclosure by conducting a quantitative study of Indonesia’s manufacturing companies listed on the Indonesia Stock Exchange in the year 2017-2019. This issue attracted the researcher to deeply examine the relationship between the companies’ financial performance and CSR disclosure in their annual reports by considering their financial performance measurement, including the company’s profitability (Return on Equity), Leverage (Debt to Assets), and Firm Size. To examine those measurements, this research also adopted the General Reporting Initiative (GRI) based on the checklist of Corporate Social Responsibility disclosure items that companies had disclosed in their annual report. In this research, data were collected by obtaining the 146 companies’ annual reports for 2017-2019 of all manufacturing companies listed in the Indonesia Stock Exchange via the website www.idx.co.id and analyzing the annual report to determine the suitable companies and all the data regarding the characteristics of the purposive sampling method. Thirty manufacturing companies that fulfilled all the criteria were included as samples to obtain the data for this research. As a result, this research showed that all of the variables of company’s profitability (Return on Equity), Leverage (Debt to Assets), and Firm Size affected the Corporate Social Responsibility Disclosure.